Turkey and the European Union: Divergent Discourses? - Edward Moxon-Browne; Cigdem Ustun (Romanian Journal of European Affairs, 2009)
It has become almost axiomatic to argue that the prospect of Turkish accession to the European Union (EU) poses unprecedented challenges to its cohesion, its institutional structure, and to its identity. No country has waited longer to open negotiations with the EU, and no country has embarked on negotiations with such a distant prospect for those negotiations being concluded. Our purpose here is not to consider the wide range of problems faced by Turkey in these negotiations, or even to make a judgement on whether these negotiations will, or ought to be, successful. Our objective is to consider public opinion in the EU, and in Turkey with a view to isolating perceptions on both sides that may be complicating factors in an already intricate relationship.